Evaluation of Head Trauma: Efficacy of Skull Films - Masters, Stuart J. (American Journal of Neuroradiology, 1980)
A retrospective review of 1,845 patients was performed to evaluate the efficacy of skull films in acute head trauma. The implications of efficacy included effects on diagnosis, therapy, and ultimate outcome. Seventy-nine patients had skull fractures. Thirty-three patients sustained significant intracranial sequelae from their injuries, but only seven of these also sustained fractures. Twenty-six patients had significant intracranial sequelae but no skull fracture. In none of the 33 patients with significant intracranial sequelae was management or outcome affected by skull film findings. Of 1,845 patients, seven (0.38%) had basilar fractures requiring antibiotics. These were the only patients whose treatment and outcome were apparently altered by radiographic findings. Skull fractures alone seldom indicate more serious internal head injury. Routine skull films after head trauma are not effective contributors to the evaluation, management, or outcome of acute intracranial injury. “High-yield” clinical criteria are offered for predicting patients at risk for significant intracranial sequelae. If any of the “high-yield” features for significant intracranial sequelae are present, computed tomography should be considered as the primary, noninvasive diagnostic procedure of choice. The poor correlation of skull fracture with significant intracranial sequelae suggests that, for a select subgroup of patients, skull fracture may protect against significant intracranial sequelae.